Geografi Ekonomi Perawatan dalam Mobilitas Gender: Narasi Perjalanan Solo Perempuan Indonesia - Hidayati, Inayah; Mardian, Andry; Mufdalifah, Inka Winarni; Nugraha, Rd. Deden Gumilar (Journal of Geographical Sciences and Education, 2025)
Women’s mobility in urban spaces is often constrained by gender norms, yet solo travel creates opportunities to renegotiate care, identity, and everyday geographies across multiple scales of mobility. This study examines 25 cases of Indonesian women’s international solo travel as an extension of the care economy, drawing on feminist epistemology and a narrative approach. Solo travel is a form of self-care that restores emotional balance, fosters resilience, and affirms women’s right to time and space. It functions as a spatial negotiation of access to public space, mobility, and autonomy across multiple scales, from household constraints to transnational journeys. The Indonesian context adds distinctive dimensions were cultural and religious norms, expectations of modesty, and family negotiations intersect with urbanization, middle-class expansion, and global exposure to shape how women claim legitimacy in mobility. This study represents both a personal and spatial practice of resistance, enriching Global South debates on the care economy and Geography.